Intelligent Data Analysis and Applications Proceedings of the Third Euro-China Conference on Intelligent Data Analysis and Applications, ECC 2016 - Pan, Jeng-Shyang.; Snášel, Václav; Sung, Tien-Wen.; Wang, Xiao Dong.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book gathers papers presented at the ECC 2016, the Third Euro-China Conference on Intelligent Data Analysis and Applications, which was held in Fuzhou City, China from November 7 to 9, 2016. The aim of the ECC is to provide an internationally respected forum for scientific research in the broad areas of intelligent data analysis, computational intelligence, signal processing, and all associated applications of artificial intelligence (AI). The third installment of the ECC was jointly organized by Fujian University of Technology, China, and VSB-Technical University of Ostrava, Czech Republic. The conference was co-sponsored by Taiwan Association for Web Intelligence Consortium, and Immersion Co., Ltd.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence